Case report and literature review: tislelizumab combined with lenvatinib and polymeric micellar paclitaxel for thymic squamous cell carcinoma - Chen, Jingwen; Wang, Yihan; Shou, Minyue; Qian, Jieyi; Ma, Ling; Shu, Yongqian (Frontiers in Immunology, 2025)
Thymic squamous cell carcinoma (TSCC) is a rare malignancy with an annual incidence of 0.15–0.32 per 100,000 population and exhibits aggressive behavior including early metastasis. Anti-PD-1 immunotherapy combined with chemotherapy has emerged as a potential strategy for TSCC. We report a 60-year-old male with a 1-month history of persistent dry cough and generalized fatigue. Diagnostic evaluation revealed advanced TSCC (cT3N2M1b), with bilateral lung, right pleural, left adrenal, mediastinal and right hilar lymph nodes metastases. Significantly elevated CA125 and CYFRA211 levels were observed. Initial first-line carboplatin plus polymeric micellar paclitaxel (PM-PTX) stabilized the disease. Subsequent adjustments to the immunotherapy regimen led to a two-phase approach combining tislelizumab, lenvatinib, PM-PTX, with or without carboplatin. This strategy achieved sustained tumor burden reduction with improved quality of life and nutritional status throughout treatment, without significant immune-related adverse events (irAEs). Additionally, we discuss the mechanisms of combination therapy, immunotherapy toxicities in thymic malignancies, and propose personalized combination strategies to guide clinicians in selecting treatment options.